Low tech hacking : street smarts for security professionals - Wiles, Jack; Gudaitis, Terry; Jabbusch, Jennifer; Rogers, Russ; Lowther, Sean (Syngress, 2012)
Criminals using hacking techniques can cost corporations, governments, and individuals millions of dollars each year. While the media focuses on the grand-scale attacks that have been planned for months and executed by teams and countries, there are thousands more that aren't broadcast. Low Tech Hacking focuses on the everyday hacks that, while simple in nature, actually add up to the most significant losses. Attackers are using common techniques like social engineering, wireless hacking, and targeting and surveillance to gain access to valuable data. This book contains detailed descriptions.